Comparative evaluation of osteogenic activity and the effect on hematopoietic function of bone marrow of fractions of Saussurea controversa and Filipendula ulmaria extracts in experimental osteomyelitis - E. Yu. Avdeeva; M. G. Skorokhodova; I. V. Sukhodolo; E. D. Porokhova; G. V. Slizovsky; L. S. Mushtovatova; Ya. E. Reshetov; S. D. Ivanov; M. V. Belousov (Бюллетень сибирской медицины)
The aim of the work was to study the effect of fractions from Saussurea controversa and Мeadowsweet extracts on hemopoiesis and regeneration of bone tissue, which are the main target indicators in experimental osteomyelitis.Materials and methods. In the experiment we used butanol, water and element-organic fractions from the Saussurea controversa extract as well as ethyl acetate, butanol and water fractions from the Мeadowsweet extract, obtained by liquid extraction of the extracts from corresponding plants with the help of organic solvents. After modeling osteomyelitis of the right femur in rats and course treatment for 28 days, the state of bone marrow hemopoiesis was evaluated and morphological examination of the affected limb was performed.Results. The butanol fraction (at a dose of 10 mg/kg) containing flavonol glycosides, the water fraction (at a dose of 80 mg/kg) containing polysaccharides in its composition and the element-organic fraction (at a dose of 10 mg/kg) represented by organic calcium showed the highest osteogenic activity in the Saussurea controversa extract. The water fraction from the Meadowsweet extract (at a dose of 50 mg/kg) demonstrated pronounced hemopoietic activity due to stimulating erythro-, granulo- and lymphopoiesis in the bone marrow of rats with experimental osteomyelitis.